The Dutch Reformed Church and the Faculty of Theology at the University of Pretoria - Du Toit, Philippus R. (Verbum et ecclesia, 2009)
The focus of this article is on the fundamental and practical reasons that led to the establishment of theological training by the Dutch Reformed Church in the northern part of South Africa. The Faculty of Theology (Division B) was eventually established in 1938 at the University of Pretoria - nearly 80 years since the opening of the Theological Seminary in Stellenbosch. Attention is given both to the major role players in Church and Faculty as well as to the developments that inf uenced both Church and Faculty: the Dutch Reformed Church of Transvaal eventually dissolved into four synods; the Faculty of Theology on the other hand united the two Divisions to become one multi-denominational faculty in 2000. Cognisance is taken of the major tensions between faculty and Church during the course of time. Special attention is given to certain accusations regarding theological heresy during the last decade.